2019
DOI: 10.1080/15350770.2018.1535343
|View full text |Cite
|
Sign up to set email alerts
|

A Multinational Comparison of Grandchildren’s Received Affection from Their Grandparents

Abstract: This study sought to address the need for systematic, quantitative cross-cultural comparisons to extend our knowledge of the interplay between cultural backgrounds and human behaviors. Specifically, in this study, we compared young adult Danish, Icelandic, Polish, and American grandchildren's reports of received affection from their grandparents. The participants (N = 606) completed the Grandchildren's Received Affection Scale. Results of a multivariate analysis of variance (MANOVA) revealed significant cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The purpose of this study was to assess the reliability and validity (i.e., factorial, construct) of the French version of the Grandchildren's Received Affection Scale (GRAS). In line with the original model (Mansson, 2013d) as well as a study conducted among Danish, Icelandic, Polish and American grandchildren (Mansson & Sigurðardóttir, 2019), the four dimensions of the French GRAS (i.e., love and esteem, caring, memories and humor, and celebratory affection) were validated in this study, which gives researchers the possibility to study affectionate communication received by Frenchspeaking grandchildren from their grandparents. The factorial validity of the scale was confirmed.…”
Section: Discussionmentioning
confidence: 84%
“…The purpose of this study was to assess the reliability and validity (i.e., factorial, construct) of the French version of the Grandchildren's Received Affection Scale (GRAS). In line with the original model (Mansson, 2013d) as well as a study conducted among Danish, Icelandic, Polish and American grandchildren (Mansson & Sigurðardóttir, 2019), the four dimensions of the French GRAS (i.e., love and esteem, caring, memories and humor, and celebratory affection) were validated in this study, which gives researchers the possibility to study affectionate communication received by Frenchspeaking grandchildren from their grandparents. The factorial validity of the scale was confirmed.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies already reported high levels of grandparental affection received by emerging adults (Mansson & Sigurðardóttir, 2019). Affection exchange theory (AET) could bring light on this result as grandchildren who reach emerging adulthood develop strong interpersonal relationships and become more likely to procreate.…”
Section: Celebratorymentioning
confidence: 99%
“…The overuse of white WEIRD samples limits understanding of how affectionate communication and the association between affectionate communication and health vary across countries and cultures. As one exception, Mansson and Sigurðard ottir (2017) reported that U.S. Americans enacted more affectionate behavior than participants from other countries (Iceland, Denmark, and Poland; see also Mansson et al, 2016;Mansson & Sigurðard ottir, 2019). That said, their affection scales were created based on research conducted in the United States, legitimately raising the question of what role measurement played in their findings.…”
Section: White and Weirdmentioning
confidence: 99%